Penggunaan Media Sosial Facebook, Twitter Dan Youtube Untuk Membangun Consumer Brand Relationship Oleh Merek-Merek Di Indonesia - Ardi Meidianto Putra (Trunojoyo University of Madura, 2021)
One way for marketers to build Consumer-brand relationship is by creating brand accounts in social media, such as Facebook, Twitter, and YouTube. In addition, many brands are using social media to build a relationship through interaction with Consumers but have not made the best use of social media, ranging from how to make a brandpost according to the needs of Consumers that will generate a positive response from Consumers to the liveliness of the brands in providing response of the comments made by the Consumer. The data was obtained from brandposts on Facebook, Twitter and YouTube. The total of the brandposts are 2040 of 10 goods and services brands in Indonesia. Results show that brands are tend to post more informational brandposts than entertainment brandposts in building Consumer brand relationship. There is a difference between the forms of interactivity brandpost and the number of Consumer’s response and also a difference between informational and entertainment brandposts content to the Consumer’s comments/replies. Goods and services brand products also have some differences in building relationship with Consumers through social media. But unfortunately the brands are less responsive in answering Consumer’s comments. From 32.939 Consumer’s comments/replies, there are only 1.646 comments which are replied by the brands.